Pengaruh Aksesibilitas Dan Fasilitas Terhadap Kepuasan Pengunjung Pada Taman Satwa Cikembulan Di Kabupaten Garut - Bayu Permadi; Elga Putri Berlian; Namira Az-zahra Firdausya; Ramayani Yusuf (Lembaga Pengembangan Kinerja Dosen, 2024)
The Cikembulan Garut Animal Park tourist attraction not only offers a valuable educational resource for its visitors, but also offers a fun and entertaining experience. This positive experience can encourage visitors to spread a good message or achieve their own satisfaction. The increasing number of tourists is the easiest indicator of the success of a tourism business. If the number of tourists who come are satisfied, the number of tourists will continue to increase. In fact, the experience of visiting this tourist attraction is not able to provide satisfaction to visitors, which is indicated by the increase and decrease in the number of tourist visits to the Cikembulan Animal Park tourist attraction. The aim of this research is to determine the effect of accessibility and facilities on visitor satisfaction at the Cikembulan Garut Animal Park. The type of research is quantitative research with an associative descriptive approach with multiple regression analysis. The population in this study was all visitors who came to the Cikembulan Garut Animal Park in 2022, while the sample in this study was 100 respondents who were calculated based on the Slovin formula. The data collection method is by distributing questionnaires with a Likert scale which is part of an ordinal scale. The sampling technique uses nonprobability sampling. The results of the research show that: (1) accessibility has a significant effect on visitor satisfaction; (2) facilities have no significant effect on visitor satisfaction. Researchers suggest using new variables in future research to determine visitor satisfaction.